(untitled) (The Review of Diabetic Studies, 2020)
Diabetic wounds have a large and increasing burden on the healthcare of the UK. Currently, none of the standard treatment options for the treatment of diabetic wounds specifically target the physiological processes behind their enhanced severity. This review evaluated recent studies in the field of nanotechnology concerned with treating diabetic wounds. The studies had each developed novel therapeutics involving nanomedicines that sought to either enhance angiogenesis, the construction of new blood vessels, or increase collagen production, as well as limit the augmented inflammation, in wounds in diabetic rat or mice models. The investigations tended to either target specific antiinflammatory or pro-proliferative receptors on endogenous cells, or transport growth factors to the wound. Previous studies have shown the beneficial effects of growth factors on healing, but they are easily broken down. By transporting them in nanoscaffolds and liposomes, it has been shown that the longevity of growth factors can be enhanced. Gold nanoparticle matrices have also been shown to have a beneficial effect on healing, by both conveying proliferative factors and independently triggering angiogenesis and collagen production. The most impressive results in the review were achieved by nanomedicines involving multiple growth factors, hence, the review will highlight the beneficial factors to wound healing and suggest a composite therapy to be trialled in the future. The review will evaluate each set of papers using similar nanomedicines and highlight the challenges of transferring this therapy to the clinic.